2007
DOI: 10.1111/j.1540-5915.2007.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing Internet Product Returns: A Focus on Effective Service Operations

Abstract: Product returns present one of the biggest operational challenges in the world of Internet retailing due to the sheer volume and cost of processing returns. But returns also represent an often-missed opportunity to manage customer relationships and build customer loyalty to the retailer. Based upon data from a survey of 464 customers of five different Internet retailers, this article explores how firms' returns management systems affect loyalty intentions. We draw upon extant literature in the fields of Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
202
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(213 citation statements)
references
References 57 publications
6
202
0
3
Order By: Relevance
“…Recent research (e.g., Mollenkopf et al 2007;Yu et al 2005) has demonstrated that perceived ease of use often has only an indirect effect on behavioral intention, mediated by perceived usefulness or relative advantage. Given the conflicting findings in the literature, both direct and indirect effects of perceived ease of use on an SME's behavioral intention to adopt or continue to use the ODSC are included in our research model.…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…Recent research (e.g., Mollenkopf et al 2007;Yu et al 2005) has demonstrated that perceived ease of use often has only an indirect effect on behavioral intention, mediated by perceived usefulness or relative advantage. Given the conflicting findings in the literature, both direct and indirect effects of perceived ease of use on an SME's behavioral intention to adopt or continue to use the ODSC are included in our research model.…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…Therefore, the utility of ordering is positively influenced by the customer's expectations of the product and negatively influenced by the attached uncertainty [13,14]. To reduce the customer's perceived risk, many e-tailers offer liberal returns policies that can be considered as insurance against negative experiences [15,16]. Actively advertising these liberal policies decreases a consumer's uncertainty, thus increasing his or her overall likelihood of placing an order [17,18].…”
Section: H12cmentioning
confidence: 99%
“…Les activités analysées sont la gestion de stock (Kull et al, 2013 ;Taylor et al, 2004 ;Rabinovich 2003Rabinovich , 2004Rabinovich , 2011, les retours (Mollenkopf et al, 2007 ;Rao et al, 2014, Kokkinaki et al, 1999, le management des systèmes d'information (Waller and Fawcett, 2013 ;Wang, 2008Sanders, 2007).…”
Section: Activités Et Acteursunclassified